Analysis of health-related biomarkers between vegetarians and non-vegetarians: A multi-biomarker approach - Goran Gajski; Marko Gerić; Marijana Vučić Lovrenčić; Sandra Božičević; Ivica Rubelj; Lucia Nanić; Nikolina Škrobot Vidaček; Laila Bendix; Maja Peraica; Dubravka Rašić; Ana-Marija Domijan; Valentina Gluščić; et al. (Journal of Functional Foods, 2018)
This study was performed in a group of adult vegetarians (N = 40) and matched non-vegetarian subjects (N = 40) in order to analyse differences in health-related biomarkers. Obtained results revealed differences in various biomarkers between subjects on a traditional mixed and vegetarian diet, indicating that vegetarians have a lower nutritional status of some nutrients (Ca, Cu and Zn, and vitamins B12 and D) accompanied with a lower antioxidant defence system (glutathione) and higher homocysteine and genome damage (micronuclei and DNA strand breaks), along with shorter telomeres. This suggests that the supplementation of animal derived nutrients to this particular dietary group would be beneficial for the improvement of some measured health-related biomarkers. However, the level of certain toxic metals (As and Hg) was higher in non-vegetarians. The presented multi-biomarker approach implies the necessity of evaluating a large number of different health-related biomarkers in order to obtain clear insight into dietary preferences and health outcomes.